Growth pattern and peak growth of students aged 9 to 16 years / Kok Lian Yee, Aris Fazil Hj Ujang and Anis Mazlina Dewi Mohamed - Kok, Lian Yee; Ujang, Aris Fazil; Mohamed, Anis Mazlina Dewi (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2012)
This study aims to identify growth pattern and growth maturation of boys and girls aged between 9 to 16 years. This study is using a cross-sectional design which involved a different subject age groups and each subject represented only once as sample. The growth indicator is referred to standing height of the sample measured using stadiometer. A total of 800 students (400 boys and 400 girls) aged between 9 to 16 years participated in this study using fishbowl technique. Mean and standard deviation were used to identify the growth pattern and growth maturation of the boys and girls. Descriptive analysis showed that mean standing height of the boys and girls is increased accordingly to their age. However, mean height of the male students increased 9.7 cm rapidly at the age of 13 and 14 years. Meanwhile, mean height of the girls showed a rapid increase 7.6 cm between the age of 10 and 11 year. It can be concluded that the pattern growth of boys and girls is in line with their age. However, the peak time of growth for boys and girls are different, where the boys experienced growth peak at the age of 13 to 14 years, while the girls at the age of 10 to 11 years. In addition, boys were higher than girls, but at the age of 10 to 13 years girls were founded to be higher than boys. This is happens due to the growth process is at the peak stage at that age.